To share or not to share? The contribution of self-disclosure to stress-related growth among suicide survivors. Issue 7 (8th August 2016) - Levi-Belz, Yossi
ABSTRACT: This study examined to what extent suicide survivors can experience growth in the aftermath of suicide loss, as well as the role of self-disclosure and coping strategies in stress-related growth (SRG) among suicide survivors, compared to bereavement following sudden and expected death types. One hundred forty-five bereaved individuals (aged 18–73) completed questionnaires measuring SRG, self-disclosure, and coping strategies. Significant interaction between self-disclosure and types of death was found, in which suicide survivors with low levels of self-disclosure manifested the lowest level of SRG compared to other subgroups. This finding suggests that sharing intimate information can be beneficial in struggling with a situation of suicide in the family.